Challenges of Nursing in Better at Home Program: experience report (Research, Society and Development, 2022)
The nurse's role in public home care service must focus on the user's safe care. Thus, the objective of this report was to describe the experience of a nurse on the safety of patients assisted by the Better at Home Program (PMC), between 2016 and 2020, in a municipality on the southern coast of Bahia, pointing out potentialities and challenges encountered. During this period, she performed dressings, administered medication, checking vital signs, among others. Besides the hospital safety protocol, there was a need to develop, with the multidisciplinary team, training, preparation of a booklet, and educational conversations for the patient, family, and caregivers. Further, other strategies used were to give more effective attention to the home environment and provide the professionals' phone numbers. We concluded that the PMC provides more humanized care for being carried out at home, but may present fragility since it uses adaptations of hospital protocols, requiring greater attention from the nursing staff to ensure patient safety.